Chemotherapy activates cancer-associated fibroblasts to maintain colorectal cancer-initiating cells by IL-17A - Fiorenza Lotti; Awad Jarrar; Rish K. Pai; Masahiro Hitomi; Justin D. Lathia; Adam G. Mace; Gerald Gantt; Kumar Sukhdeo; Jennifer DeVecchio; Amit Vasanji; Patrick Leahy; Anita B. Hjelmeland; et al. (2013)
Many solid cancers display cellular hierarchies with self-renewing, tumorigenic stemlike cells, or cancer-initiating cells (CICs) at the apex. Whereas CICs often exhibit relative resistance to conventional cancer therapies, they also receive critical maintenance cues from supportive stromal elements that also respond to cytotoxic therapies. To interrogate the interplay between chemotherapy and CICs, we investigated cellular heterogeneity in human colorectal cancers. Colorectal CICs were resistant to conventional chemotherapy in cell-autonomous assays, but CIC chemoresistance was also increased by cancer-associated fibroblasts (CAFs). Comparative analysis of matched colorectal cancer specimens from patients before and after cytotoxic treatment revealed a significant increase in CAFs. Chemotherapy-treated human CAFs promoted CIC self-renewal and in vivo tumor growth associated with increased secretion of specific cytokines and chemokines, including interleukin-17A (IL-17A). Exogenous IL-17A increased CIC self-renewal and invasion, and targeting IL-17A signaling impaired CIC growth. Notably, IL-17A was overexpressed by colorectal CAFs in response to chemotherapy with expression validated directly in patient-derived specimens without culture. These data suggest that chemotherapy induces remodeling of the tumor microenvironment to support the tumor cellular hierarchy through secreted factors. Incorporating simultaneous disruption of CIC mechanisms and interplay with the tumor microenvironment could optimize therapeutic targeting of cancer.